2010
DOI: 10.2151/sola.2010-020
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Synthetic Wind Retrieval on Tropical Cyclone Structures at the Extratropical Transition Stage in the JRA-25 Reanalysis

Abstract: Structures of 266 tropical cyclones (TCs) that completed extratropical transition (ET) in the western North Pacific during 1979−2004 are examined using the JRA-25 dataset, in relation to the removal of TC wind profile retrievals (TCR) from each TC after its recurvature. The TCR is a kind of "TC bogusing" techniques, and it was expected that its removal may lead to an artificial change in the TC structure at the ET stage. Nearly half of the examined TCs have cold-core structures before the removal of the TCR. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The time when parameter B exceeds 10 during or after the recurvature is defined as the beginning (onset) of ET. Although a bogus vortex is implemented for a TC in the JRA-25 (Hatsushika et al 2006;Onogi et al 2007), termination of the bogus implementation associated with ET completion is considered to have practically no impact on the judgment of ET (Kitabatake 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The time when parameter B exceeds 10 during or after the recurvature is defined as the beginning (onset) of ET. Although a bogus vortex is implemented for a TC in the JRA-25 (Hatsushika et al 2006;Onogi et al 2007), termination of the bogus implementation associated with ET completion is considered to have practically no impact on the judgment of ET (Kitabatake 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Since the major advantage of the Japanese 25-year Reanalysis (JRA-25) dataset (Onogi et al 2007) is the representation of TC structures (Hatsushika et al 2006), we use it in this study. Although the implementation of an artificial vortex, that is a TC bogus, may result in artificial discontinuity of the storm structure before and after ET, Kitabatake (2010) demonstrated that the impact from removal of a bogus vortex at the completion of ET is very small and practically negligible.…”
Section: Introductionmentioning
confidence: 99%